Efficient design of high-level mechanisms for hard safety-critical low-power devices - Michail, Harris; Kakarountas, Athanasios P.; Kokkinos, Vasileios (My University, 2005)
The introduction of high-level sophisticated mechanisms can bridge the gap in the field of safety-critical applications design and the low-power design. Two modified mechanisms that allow event driven operation with respect to safety requirements and on-line testing are presented. An optimized instruction-opcode mapping algorithm for application specific capable processing units is also introduced to assist the above mechanisms. The whole work has been applied to a commercial product and a 40% of power saving has been achieved.
Keywords: Algorithms; Microcontrollers; Commercial products